Field notes contributed by Gerald White, spring 1984 - White, Geraldet al (1984)
Field notes were contributed by Gerald White, spring 1984. He sighted five species in Cedar Rapids or at Cone Marsh. In a cover letter to Thomas H. Kent, he explained that the American Bittern had a leg defect that would make it identifiable, May 24, 1984. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1984. Epson - sheet feed/flatbed